The dynamic link between financial development, trade openness and foreign direct investment: empirical evidence from Ethiopia / Mekuanent Tesega - Tesega, Mekuanent (Universiti Teknologi MARA, 2021)
Foreign direct investment (FDI) is an important source of external financing and an important factor for the economic development of a country. FDI is highly important especially for developing countries as it brings modern technologies and management skills in addition to narrowing the financial gaps. In this sense the knowledge of what determines FDI will have a tremendous significance. With the objective of empirically determining the long-run and short-run relationships between financial development, trade openness and FDI inflows in Ethiopia this study employed the ARDL model. The findings indicated that private sector credit, M2 and trade openness have a positive and significant influence on FDI inflows in the long-run while M2, and trade openness has a positive and significant influence on FDI in the short-run too. Current period private sector credit had no impact on FDI while the one period lag of it has a positive significant effect on FDI. Likewise, the causality test results disclose the presence of bi-directional causal relationships between private sector credit and FDI, and between M2 and trade openness. Furthermore, the findings indicate a one direction Granger cause from M2 to FDI. Policy makers are advised to consider trade openness and financial development measures in their quest for more FDI inflow.